Nilai Pendidikan Karakter Tokoh Sarwono Film Hujan Bulan Juni dan Aplikasinya sebagai Alternatif Materi Ajar Sastra - Wiga Adhi Yudha; Mukti Widayati; Nurnaningsih Nurnaningsih (Journal on Education, 2023)
Abstract: This study aims to describe (1) aspects of the character of Sarwono's character in the film Rain of the Month of June, (2) the educational value of the character of Sarwono in the film Rain of the Month of June, (3) the application of the educational value of the character of Sarwono in the film Rain of the Month of June as an alternative literary material. This type of research is a descriptive qualitative research with a research approach using embedded and case studies. The research data are in the form of the speech and actions of Sarwono's character in the film Rain of the Month of June, and the results of interviews with teacher sources. Sources of data in the form of learning device documents, teacher resource persons, the film Rain of the Month of June. Data collection techniques by observation, in-depth interviews, document analysis, listen and record. The data validation technique uses source triangulation and method triangulation. The interactive data analysis technique starts from data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the educational value of Sarwono's character in the film Rain Month June obtained 18 values of character education, namely (1) Religious, (2) Honesty, (3) Tolerance, (4) Hard work, (5) Discipline, (6) Creative, (7) Independence, (8) Awareness of the rights and obligations of others, (9) Curiosity, (10) National Spirit, (11) Love for the country, (12) Appreciating Achievements, (13) Communicative, ( 14) Love of peace, (15) Loves to read, (16) Cares for the environment, (17) Cares for social, (18) Responsibility. The results of the application of the educational value of the character of Sarwono's character in the film Rain of the Month of June as an alternative material for teaching literature on the practice of applying learning are adapted to the condition of students and imitate every behavior that is carried out by the character of Sarwono in the film Rain of the Month of June.